A silicon-carbon negative electrode material and preparation method thereof and lithium-ion battery

By using silicon-carbon anode material in lithium-ion batteries and using molten salt electrochemical method to generate nano-silicon and carbon composite materials, the stability and capacity problems of graphite anode material are solved, and efficient and stable lithium-ion battery performance is achieved.

CN119764409APending Publication Date: 2025-04-04JIANGSU TANSHI TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411973676.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The negative electrode material graphite of existing lithium-ion batteries cannot meet the needs of long-term large-capacity power supply for electronic devices due to its unstable layered structure, low theoretical capacity, high irreversible capacity and poor deintercalation lithium magnification performance.

Method used

Using a silicon-carbon negative electrode material, a silicon-carbon material with nano-silicon deposited is generated by placing a silicon-carbon composite precursor in the molten electrolyte to apply a voltage, and a silicon-carbon material is combined with a carbon material to buffer volume changes and improve conductivity.

Benefits of technology

It improves the cycle stability of lithium-ion batteries, first charge and discharge efficiency, and volume change rate when embedded/removing lithium, and meets the battery needs of high capacity and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764409A_ABST
    Figure CN119764409A_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-carbon negative electrode material, a preparation method thereof and a lithium-ion battery, and belongs to the technical field of negative electrode materials. The carbon negative electrode material comprises a carbon material and nano-silicon deposited on the surface of the carbon material; the content of nano-silicon in the silicon-carbon negative electrode material is 1wt% to 10wt%, and the nano-silicon is prepared by nano-silicon oxide through a molten salt electrochemical method. When the silicon-carbon negative electrode material is used as a negative electrode material of a lithium-ion battery for charging and discharging, the silicon-carbon negative electrode material can inhibit the volume change when silicon is deintercalated with lithium and improve the conductivity of the material, showing good electrochemical properties, such as specific capacity and cycle retention rate. The preparation of the silicon-carbon negative electrode material comprises: preparing a carbon material with nano-silicon oxide deposited on the surface into a cathode, placing it together with an anode in a molten electrolyte, and applying a voltage to obtain a silicon-carbon material with nano-silicon deposited on the cathode. The method is simple to operate, highly feasible, and low in cost, and is easy to realize large-scale production of silicon-carbon composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, good charge and discharge cycle stability and green environmental protection. They are important energy storage devices for portable electronic devices and electric vehicles. Most commercial lithium-ion batteries use graphite as the negative electrode. Although graphite has the characteristics of low cost, abundant raw materials and high conductivity, the layered structure of graphite is unstable, the theoretical capacity is low (about 372mAh / g), the irreversible capacity is high, and the lithium deintercalation rate performance is poor. It cannot meet the long-term large-capacity power supply needs of electronic devices, which limits the long-term development of lithium-ion batteries. Therefore, it is urgent to develop high-capacity and stable performance negative electrode materials to replace graphite.

[0003] Silicon is expected to become the negative electrode material of the new generation of lithium-ion batteries due to its high specific capacity, abundant reserves, and low lithium insertion and extraction potential. However, during the charging and discharging process, the insertion and extraction of lithium in silicon will cause the volume of silicon to change by 300% to 400%. The stress generated can easily cause the active material of the electrode to pulverize, separate the material from the current collector, and lose electrical contact, causing its capacity to decay rapidly.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof and a lithium-ion battery to solve or improve the above-mentioned technical problems.

[0006] The present invention can be implemented like this:

[0007] In the first aspect, the present invention provides a silicon-carbon negative electrode material, which includes a carbon material and nano-silicon deposited on the surface of the carbon material; the content of nano-silicon in the silicon-carbon negative electrode material is 1wt% to 10wt%, and the nano-silicon is prepared from nano-silicon oxide by molten salt electrochemical method.

[0008] In a second aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material as in the aforementioned embodiment, comprising the following steps: preparing a silicon oxide-carbon composite precursor into a cathode, placing the cathode and the anode together in a molten electrolyte, applying a voltage to the cathode and the anode to obtain a silicon-carbon material with nano-silicon deposited on the cathode;

[0009] The silicon oxide-carbon composite precursor is a carbon material with nano silicon oxide deposited on the surface.

[0010] In an optional embodiment, the preparation of the silicon oxide-carbon composite precursor includes: mixing a silicon source and an acid-treated carbon material in an aqueous solvent to hydrolyze the silicon source to obtain a carbon material with nano-silicon oxide deposited on the surface.

[0011] In an alternative embodiment, the silicon source includes at least one of organic silicon compounds that can be hydrolyzed to form silicon oxide.

[0012] In an optional embodiment, the mass ratio of the silicon source to the acid-treated carbon material is 0.001:1 to 0.95:1.

[0013] In an alternative embodiment, the volume ratio of the aqueous solvent to the silicon source is 200:1 to 5000:1.

[0014] In an alternative embodiment, the aqueous solvent comprises anhydrous ethanol and water in a volume ratio of 8:1 to 12:1.

[0015] In an optional embodiment, the preparation of the acid-treated carbon material comprises: acid-treating the carbon material with an acid, followed by drying.

[0016] In an alternative embodiment, the carbon material includes at least one of graphite, carbon nanotubes, and amorphous carbon.

[0017] In an alternative embodiment, the acid comprises at least one of concentrated nitric acid and concentrated sulfuric acid.

[0018] In an optional embodiment, the temperature of the acidification treatment is 80°C to 120°C.

[0019] In an optional embodiment, the acidification treatment is carried out under stirring conditions; preferably, the stirring time is 20 h to 28 h.

[0020] In an optional embodiment, mixing the silicon source with the acid-treated carbon material in an aqueous solvent comprises: firstly ultrasonically mixing the acid-treated carbon material with the aqueous solvent to obtain a carbon dispersion; adjusting the hydroxide ion concentration of the carbon dispersion to 10 -1 mol / L~10 -3 mol / L; then add silicon source and continue stirring, then separate the solid and liquid and dry.

[0021] In an alternative embodiment, the hydroxide ion concentration of the carbon dispersion is adjusted by adding an alkaline solution to the carbon dispersion.

[0022] In an optional embodiment, the alkaline solution includes at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide.

[0023] In an optional embodiment, the stirring time is continued for 20 hours to 30 hours.

[0024] In an optional embodiment, preparing the silicon oxide-carbon composite precursor into a cathode includes: fixing the silicon oxide-carbon composite precursor to a current collector;

[0025] In an alternative embodiment, the current collector is a metallic conductor.

[0026] In an alternative embodiment, the metal conductor comprises at least one of stainless steel, mild steel, nickel, copper and molybdenum.

[0027] In an alternative embodiment, the anode is an inert electrode.

[0028] In an alternative embodiment, the anode comprises at least one of graphite, tin oxide, and an inert alloy.

[0029] In an alternative embodiment, the electrolyte comprises a monovalent or polyvalent mixed salt of a chloride salt or a fluoride salt.

[0030] In an alternative embodiment, the chloride salt comprises at least one of CaCl2, LiCl, NaCl and KCl.

[0031] In an alternative embodiment, the fluoride salt comprises at least one of CaF2, LiF, NaF and KF.

[0032] In an optional embodiment, the electrolyte is first subjected to a pre-electrolysis treatment, and then the cathode and the anode are placed together in the pre-electrolysis treated and molten electrolyte.

[0033] In an optional embodiment, the voltage used for the pre-electrolysis treatment is 1V to 3V, and the time is 3h to 12h.

[0034] In an alternative embodiment, the temperature of the molten electrolyte is 400°C to 1000°C.

[0035] In an alternative embodiment, the applied voltage is above the precipitation voltage of silicon in silicon oxide and below the precipitation voltage of alkali metals in molten electrolyte.

[0036] In an optional implementation, the voltage is 1.5V to 3.5V.

[0037] In an optional embodiment, the voltage is applied for a period of 1 hour to 24 hours.

[0038] In a third aspect, the present invention provides a lithium-ion battery, which includes the silicon-carbon negative electrode material of the aforementioned embodiment.

[0039] The beneficial effects of the present invention include:

[0040] The present invention nanosizes silicon to increase its specific surface area, which can alleviate structural cracking and mechanical pulverization during lithium insertion and extraction; accelerates the infiltration of battery electrolyte while shortening the diffusion distance of lithium ions. The silicon-carbon composite material generated by combining nano-silicon and carbon materials can further buffer the stress generated by volume change and improve the conductivity of the material, thereby improving the cycle stability of lithium-ion batteries. The silicon-carbon negative electrode material provided by the present invention has the characteristics of high initial charge and discharge efficiency, stable cycle performance, and low volume change rate when inserting / extracting lithium.

[0041] In addition, the present invention adopts a molten salt electrochemical method, by placing an anode and a cathode prepared from a silicon oxide-carbon composite precursor in a molten electrolyte, applying a voltage to the two electrodes, and the silicon oxide in the precursor is deoxidized by electrons to generate silicon, and the generated silicon is in situ composited with carbon, and a silicon-carbon negative electrode material with nano-silicon deposited can be directly obtained at the cathode, and the silicon in the silicon-carbon negative electrode material exists in the form of elemental silicon. Silicon oxide and carbon materials are mixed as precursors, and carbon can greatly improve the conductivity of the precursor. Compared with pure SiO2, when deoxidation is required, electrons need to be transferred through the generated silicon. The silicon oxide in the silicon oxide-carbon precursor can transfer electrons through carbon, and the oxygen in the precursor can be completely removed to generate silicon. In situ composite with carbon material can directly generate silicon-carbon composite materials. In addition, the above-mentioned molten salt electrochemical method can greatly simplify the synthesis process of silicon-carbon composite materials and improve the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0043] Figure 1 This is a scanning electron microscope image of the silicon-carbon negative electrode material prepared in Example 1;

[0044] Figure 2 The X-ray energy dispersion spectrum of the surface of the silicon-carbon negative electrode material prepared in Example 1;

[0045] Figure 3 The X-ray diffraction pattern of the silicon-carbon negative electrode material prepared in Example 1;

[0046] Figure 4 This is a cycle performance diagram of the silicon-carbon negative electrode material prepared in Example 1 as a negative electrode for a lithium-ion battery at a current density of 100 mA / g;

[0047] Figure 5The charge and discharge curve of the silicon-carbon negative electrode material prepared in Example 1 as a negative electrode of a lithium-ion battery within 100 cycles at a current density of 100 mA / g;

[0048] Figure 6 The figure is a rate performance diagram of the silicon-carbon negative electrode material prepared in Example 1 as a negative electrode of a lithium-ion battery within 100 cycles at different current densities;

[0049] Figure 7 This is a scanning electron microscope image of the silicon-carbon negative electrode material prepared in Example 2;

[0050] Figure 8 This is a cycle performance diagram of the silicon-carbon negative electrode material prepared in Example 2 as a negative electrode for a lithium-ion battery at a current density of 100 mA / g;

[0051] Fig. 9 The SEM images of the precursor and silicon-carbon negative electrode material prepared in Example 3 are shown;

[0052] Fig.10 The X-ray energy dispersion spectrum of the surface of the silicon-carbon negative electrode material prepared in Example 3;

[0053] Fig.11 This is a graph showing the cycling performance of the silicon-carbon negative electrode material prepared in Example 3 as a negative electrode for a lithium-ion battery at a current density of 100 mA / g. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0055] The silicon-carbon negative electrode material and its preparation method and the lithium-ion battery provided by the present invention are specifically described below.

[0056] The invention provides a silicon-carbon negative electrode material, which comprises a carbon material and nano-silicon deposited on the surface of the carbon material; the content of the nano-silicon in the silicon-carbon negative electrode material is 1wt% to 10wt%, and the nano-silicon is prepared from nano-silicon oxide by a molten salt electrochemical method.

[0057] Among them, the content of nano-silicon in the silicon-carbon negative electrode material can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc., or it can be other values ​​within the range of 1wt% to 10wt%.

[0058] If the content of nano-silicon in the silicon-carbon negative electrode material is less than 1wt%, the initial efficiency and capacity of the lithium-ion battery using it as the negative electrode will be low, reducing the energy density of the battery; if the content of nano-silicon in the silicon-carbon negative electrode material exceeds 10wt%, silicon will undergo a dramatic volume expansion during the lithiation process, affecting the cycle life and safety of the battery.

[0059] The present invention nanosizes silicon to increase its specific surface area, which can alleviate structural rupture and mechanical pulverization during lithium insertion and extraction, accelerate the infiltration of battery electrolyte and shorten the diffusion distance of lithium ions. The silicon-carbon composite material generated by combining nano-silicon and carbon material can further buffer the stress generated by volume change and improve the conductivity of the material, thereby improving the cycle stability of lithium-ion batteries. The silicon-carbon negative electrode material provided by the present invention has the characteristics of high initial charge and discharge efficiency, stable cycle performance and low volume change rate when inserting / extracting lithium.

[0060] In some optional embodiments, the specific capacity of the silicon-carbon negative electrode material is not less than 400 mAh / g. In some typical embodiments, the specific capacity of the silicon-carbon negative electrode material can be 400 mAh / g to 800 mAh / g.

[0061] In some optional embodiments, the capacity retention rate of the silicon-carbon negative electrode material can reach 98% after 200 cycles.

[0062] Accordingly, the present invention also provides a method for preparing the above-mentioned silicon-carbon negative electrode material, which may include the following steps: preparing a silicon oxide-carbon composite precursor into a cathode, placing it together with an anode in a molten electrolyte, and applying voltage to the cathode and the anode to obtain a silicon-carbon material with nano-silicon deposited on the cathode. The above-mentioned silicon oxide-carbon composite precursor is a carbon material with nano-silicon oxide deposited on the surface.

[0063] It should be noted that the commonly used methods for synthesizing silicon-carbon composite materials include chemical vapor deposition, high-energy ball milling, pyrolysis and hydrothermal methods. These methods have more or less the characteristics of complicated processes, high costs, low yields and low product purity, which limits the large-scale commercial application of silicon-carbon composite materials.

[0064] The present invention adopts a molten salt electrochemical method, and by mixing silicon oxide and carbon materials as precursors, carbon can greatly improve the conductivity of the precursor. Compared with pure SiO2, which needs to transfer electrons through the generated silicon during deoxidation, the silicon oxide in the silicon oxide-carbon precursor can transfer electrons through carbon, and the oxygen in the precursor can be completely removed to generate silicon, which can be directly generated by in-situ compounding with carbon materials. In addition, the above-mentioned molten salt electrochemical method can greatly simplify the synthesis process of silicon-carbon composite materials and improve the purity of the product.

[0065] In some optional embodiments, preparing the silicon oxide-carbon composite precursor into a cathode includes: fixing the silicon oxide-carbon composite precursor to a current collector. The current collector is a metal conductor, for example, may include at least one of stainless steel, low carbon steel, nickel, copper and molybdenum.

[0066] In some optional embodiments, the preparation of the silicon oxide-carbon composite precursor may include: mixing a silicon source and an acid-treated carbon material in an aqueous solvent to hydrolyze the silicon source to obtain a carbon material with nano silicon oxide deposited on the surface.

[0067] Preferably, the acidified carbon material is firstly ultrasonically mixed with an aqueous solvent to obtain a carbon dispersion; and the hydroxide ion concentration of the carbon dispersion is adjusted to 10 -1 mol / L~10 -3 mol / L (e.g. 10 -1 mol / L、10 -2 mol / L or 10 - 3 mol / L, etc.); then adding a silicon source and stirring continuously to hydrolyze the silicon source, followed by solid-liquid separation and drying to obtain a carbon material with nano-silicon oxide deposited on the surface.

[0068] In some optional embodiments, the preparation of the acid-treated carbon material may include: acid-treating the carbon material with an acid, followed by drying.

[0069] The carbon material may exemplarily include at least one of graphite, carbon nanotubes and amorphous carbon. The acid may exemplarily include at least one of concentrated nitric acid and concentrated sulfuric acid.

[0070] The temperature of the acidification treatment may be 80°C to 120°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, etc., or other values ​​within the range of 80°C to 120°C.

[0071] Preferably, the acidification treatment is carried out under stirring conditions, and the stirring time can be 20 h to 28 h, such as 20 h, 22 h, 24 h, 26 h or 28 h.

[0072] Drying after the acidification treatment can be carried out by vacuum drying.

[0073] In some optional embodiments, the silicon source includes at least one of organic silicon compounds that can be hydrolyzed to generate silicon oxide, for example, can include at least one of tetraethyl silicate (TEOS), triethylsilane and trichlorosilane.

[0074] The mass ratio of the silicon source to the acid-treated carbon material can be 0.001:1 to 0.95:1, such as 0.001:1, 0.01:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1 or 0.95:1, or other values ​​within the range of 0.001:1 to 0.95:1.

[0075] The volume ratio of the aqueous solvent to the silicon source may be 200:1 to 5000:1 (e.g., 200:1, 500:1, 1000:1, 2000:1, 3000:1, 4000:1, or 5000:1). The aqueous solvent may include anhydrous ethanol and water in a volume ratio of 8:1 to 12:1 (e.g., 8:1, 9:1, 10:1, 11:1, or 12:1).

[0076] The ultrasonic mixing time can be 10 min to 60 min, such as 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, etc., or other values ​​within the range of 10 min to 60 min.

[0077] The hydroxide ion concentration of the carbon dispersion can be adjusted by adding an alkaline solution to the carbon dispersion, wherein the alkaline solution can illustratively include at least one of ammonia water, sodium hydroxide and potassium hydroxide.

[0078] The stirring time can be 20 h to 30 h, such as 20 h, 24 h, 28 h or 30 h.

[0079] As mentioned above, by subjecting the carbon material to acid treatment, the surface of the carbon material can be etched to cause defects on the surface, which is conducive to the coating of nano-silicon oxide particles; after the silicon source is hydrolyzed under alkaline conditions, the generated nano-silicon oxide can be effectively coated on the surface of the defective carbon material during continuous stirring.

[0080] In some optional embodiments, the anode used in the molten salt electrochemical treatment process is an inert electrode, for example, may include at least one of graphite, tin oxide and an inert alloy.

[0081] The electrolyte may include a monovalent or polyvalent mixed salt of a chloride salt or a fluoride salt. The chloride salt may exemplarily include at least one of CaCl2, LiCl, NaCl and KCl. The fluoride salt may exemplarily include at least one of CaF2, LiF, NaF and KF.

[0082] In some optional embodiments, the electrolyte is first subjected to a pre-electrolysis treatment, and then the cathode and the anode are placed together in the electrolyte that has been subjected to the pre-electrolysis treatment and is in a molten state.

[0083] The pre-electrolysis treatment may be to pre-electrolyze the electrolyte together with another cathode and anode, wherein the cathode used in the pre-electrolysis treatment may be a metal material with high porosity (such as nickel foam, copper foam, etc.), and the anode used in the pre-electrolysis treatment may be graphite or an inert electrode. The voltage used in the pre-electrolysis treatment is 1V to 3V (such as 1V, 1.5V, 2V, 2.5V or 3V, etc.), and the time is 3h to 12h (such as 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.).

[0084] Through pre-electrolysis treatment, moisture and impurities in the electrolyte can be removed to avoid affecting the subsequent molten salt electrochemical reaction.

[0085] In some optional embodiments, the temperature of the molten electrolyte may be 400°C to 1000°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, etc., or other values ​​within the range of 400°C to 1000°C.

[0086] In some optional embodiments, during the molten salt electrochemical reaction, the applied voltage is higher than the precipitation voltage of silicon in silicon oxide and lower than the precipitation voltage of alkali metals in the molten electrolyte. In some typical embodiments, the voltage is 1.5V to 3.5V, such as 1.5V, 2V, 2.5V, 3V or 3.5V, etc., or other values ​​within the range of 1.5V to 3.5V. The duration of the applied voltage can be 1h to 24h, such as 1h, 2h, 4h, 8h, 12h, 16h, 20h or 24h, etc., or other values ​​within the range of 1h to 24h.

[0087] In some optional embodiments, the molten salt electrochemical reaction can be that the electrolyte is placed in a crucible and placed in a stainless steel reactor. Under a protective gas atmosphere, the reactor is heated until the electrolyte is in a molten state. The cathode and anode are then placed in the molten electrolyte and a constant voltage is applied. Under the action of the voltage, the silicon oxide in the cathode gains electrons and is deoxidized to form silicon, and at the same time, it is in situ compounded with the carbon material to form a silicon-carbon negative electrode material.

[0088] By combining the content of nano-silicon in the silicon-carbon negative electrode material, the temperature during electrolysis, the time during electrolysis, and the voltage during electrolysis, the composition and micromorphology of the silicon-carbon negative electrode material can be regulated.

[0089] Continuing from the above, by placing an anode and a cathode prepared from a silicon oxide-carbon composite precursor in a molten electrolyte, applying voltage to the two electrodes, the silicon oxide in the precursor gains electrons and is deoxidized to generate silicon, and the generated silicon and carbon are in situ composited, and a silicon-carbon negative electrode material with nano-silicon deposited thereon can be directly obtained at the cathode, and the silicon in the silicon-carbon negative electrode material exists in the form of elemental silicon.

[0090] Furthermore, after the electrolysis is completed, the product is cooled to room temperature, repeatedly washed with dilute hydrochloric acid and deionized water, and dried.

[0091] In a third aspect, the present invention provides a lithium-ion battery, which includes the silicon-carbon negative electrode material of the aforementioned embodiment.

[0092] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0093] Example 1

[0094] This embodiment provides a silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0095] S1: 1.5 g of graphite powder was added to 125 mL of concentrated nitric acid (68 wt%) and magnetically stirred for 24 h in an oil bath at 120°C. The mixed solution was filtered and repeatedly washed with deionized water until the liquid was neutral, and then the washed graphite powder was vacuum dried at 80°C for 24 h to obtain acidified graphite powder.

[0096] S2: 20 mL of deionized water and 200 mL of anhydrous ethanol were mixed, 0.5 g of acidified graphite powder was added, and ultrasonic treatment was performed for 30 min to obtain a carbon dispersion; the carbon dispersion was magnetically stirred, and 9 mL of ammonia water (concentration of 28 wt%) was added dropwise during the stirring process, and 0.13 mL of TEOS solution (the mass ratio of TEOS to the acidified carbon material was 0.244:1) was added dropwise after 5 min and stirred for 30 h, the obtained mixed solution was filtered and washed with deionized water until the solution was neutral, and the obtained sample was vacuum dried at 80 ° C for 12 h to obtain a silicon oxide-carbon composite precursor.

[0097] S3: Weigh 500g of CaCl2-LiCl-KCl (molar ratio of 36.1:52.3:11.6), mix well and put into an alumina crucible, place the crucible containing solid chloride salt in a stainless steel reactor, heat the reactor to 300°C at a heating rate of 5°C / min, keep warm for 24h, then seal the reactor, evacuate the vacuum twice to expel the oxygen, fill with argon to maintain an inert atmosphere, then maintain the argon flow rate at 0.1L / min and heat the reactor to 650°C to make the chloride salt molten.

[0098] S4: Use pure nickel foam as cathode and graphite as anode, place the two electrodes in the molten salt obtained in S3, and apply a constant voltage of 2V to remove impurities contained in the molten salt. After 4 hours, remove the nickel foam cathode to end the pre-electrolysis process.

[0099] S5: Wrap 0.5g of the silicon oxide-carbon composite precursor obtained from S2 above with nickel foam to make a cathode, add it and a graphite anode to the molten salt in a molten state after S4 pre-electrolysis treatment, apply a voltage of 2.8V, and take out the cathode after 6 hours and cool it to room temperature. Take out the electrolytic sample from the nickel foam and soak it in 0.1mol / L dilute hydrochloric acid for 12 hours, then wash it repeatedly with deionized water and ethanol to remove the residual chloride salt. The cleaned sample is vacuum dried at 80°C for 12 hours to obtain a silicon-carbon negative electrode material.

[0100] The content of nano silicon in the silicon-carbon negative electrode material is about 3wt%.

[0101] The structure of the silicon-carbon negative electrode material was characterized, and the scanning electron microscope image is as follows Figure 1 As shown, Figure 1 b is Figure 1 The enlarged view of a in the figure; the X-ray energy dispersion spectrum is as follows Figure 2 As shown; X-ray diffraction pattern as Figure 3 shown.

[0102] Depend on Figure 1 and Figure 2 It can be seen that silicon nanowires with a diameter of 150nm are generated on the graphite surface in the silicon-carbon negative electrode material. Figure 3 It can be seen that the silicon-carbon negative electrode material is a mixture of crystalline silicon and graphite.

[0103] Example 2

[0104] The difference between this embodiment and embodiment 1 is that the amount of TEOS solution added in S2 is 0.225 mL, that is, the mass ratio of TEOS to the carbon material after acid treatment is 0.423:1.

[0105] The content of nano silicon in the silicon-carbon negative electrode material is about 5wt%.

[0106] The scanning electron microscope image of the silicon-carbon negative electrode material is shown in Figure 7 As shown, Figure 7 b is Figure 7 A magnified view of a in Figure 1. Figure 7 It can be seen that silicon nanowire clusters with a diameter of 50 nm are deposited on the graphite surface of the silicon-carbon negative electrode material.

[0107] Example 3

[0108] This embodiment provides a silicon-carbon negative electrode material, and the preparation method thereof is as follows:

[0109] S1: 1.5 g of carbon nanotubes were added to 125 mL of concentrated nitric acid (68 wt%) and magnetically stirred for 24 h in an oil bath at 120° C. The mixed solution was filtered and repeatedly washed with deionized water until the liquid was neutral, and then the washed carbon nanotubes were vacuum dried at 80° C. for 24 h to obtain acidified carbon nanotubes.

[0110] S2: 20 mL of deionized water and 200 mL of anhydrous ethanol were mixed, 0.2 g of acidified carbon nanotubes were added, and the dispersion was ultrasonically treated for 30 min to obtain a dispersion; the dispersion was magnetically stirred, and 9 mL of ammonia water (concentration of 28 wt%) was added dropwise during the stirring process, and 0.2 mL of TEOS solution (the mass ratio of TEOS to the acidified carbon material was 0.94:1) was added dropwise after 5 min and stirred for 30 h, the obtained mixed solution was filtered and washed with deionized water until the solution was neutral, and the obtained sample was vacuum dried at 80 ° C for 12 h to obtain a precursor.

[0111] S3: Weigh 500g of CaCl2-LiCl-KCl (molar ratio of 36.1:52.3:11.6), mix well and put into an alumina crucible, place the crucible containing solid chloride salt in a stainless steel reactor, heat the reactor to 300°C at a heating rate of 5°C / min, keep warm for 24h, then seal the reactor, evacuate the vacuum twice to expel the oxygen, fill with argon to maintain an inert atmosphere, then maintain the argon flow rate at 0.1L / min and heat the reactor to 650°C to make the chloride salt molten.

[0112] S4: The pre-electrolysis process of the molten salt is the same as that in Example 1.

[0113] S5: Wrap 0.2g of the precursor obtained from S2 with nickel foam to make a cathode, add it and a graphite anode to the molten salt in a molten state after S4 pre-electrolysis treatment, apply a voltage of 1.5V, and remove the cathode after 6 hours and cool it to room temperature. Take out the electrolytic sample from the nickel foam and soak it in 0.1mol / L dilute hydrochloric acid for 12 hours, then wash it repeatedly with deionized water and ethanol to remove the residual chloride salt. The cleaned sample is vacuum dried at 80°C for 12 hours to obtain a silicon-carbon negative electrode material.

[0114] The content of nano silicon in the silicon-carbon negative electrode material is about 10wt%.

[0115] The SEM images of the above precursors are shown in Fig. 9 As shown in a, the scanning electron microscope image of the silicon-carbon negative electrode material is as follows Fig. 9 As shown in b, the X-ray energy dispersion spectrum of the silicon-carbon negative electrode material is as follows Fig.10 As shown by Fig. 9 and Fig.10 It can be seen that silicon is generated on the surface of carbon nanotubes.

[0116] Example 4

[0117] The difference between this embodiment and embodiment 1 is that the electrolysis voltage used in the molten salt electro-deoxidation process is 3V.

[0118] The content of nano-silicon in the silicon-carbon negative electrode material is about 3wt%. Silicon nanowire clusters with a diameter of 50nm are also deposited on the graphite surface of the silicon-carbon negative electrode material.

[0119] Example 5

[0120] The difference between this embodiment and embodiment 1 is that the electrolyte used in the molten salt electro-deoxidation process is CaCl2-LiCl mixed salt (molar ratio is 1:1), and the molten salt temperature is 800°C.

[0121] The content of nano-silicon in the silicon-carbon negative electrode material is about 3wt%. Silicon nanowire clusters with a diameter of 50nm are also deposited on the graphite surface of the silicon-carbon negative electrode material.

[0122] Example 6

[0123] The difference between this embodiment and embodiment 1 is that the electrolyte used in the molten salt electro-deoxidation process is a 600° C. molten LiF-NaF-KF ternary mixed salt (molar ratio is 1:1:1).

[0124] The content of nano silicon in the silicon-carbon negative electrode material is about 3wt%. Silicon nanowire clusters with a diameter of 30nm are also deposited on the graphite surface of the silicon-carbon negative electrode material.

[0125] Example 7

[0126] The difference between this comparative example and Example 1 is that the amount of TEOS solution added to S2 is 0.02 ml, that is, the mass ratio of TEOS to the carbon material after acid treatment is 0.038:1.

[0127] The content of nano silicon in the generated silicon-carbon negative electrode material is about 0.5wt%. Silicon nano particles with a diameter of 20nm are generated on the graphite surface of the silicon-carbon negative electrode material and are dispersed on the graphite surface without forming silicon clusters or silicon nano wires.

[0128] Comparative Example 1

[0129] The difference between this comparative example and Example 1 is that the amount of TEOS solution added to S2 is 1 ml, that is, the mass ratio of TEOS to the acid-treated carbon material is 1.88:1.

[0130] The content of nano-silicon in the silicon-carbon negative electrode material is about 16wt%. Silicon nanowire clusters with a diameter of 30nm are generated on the graphite surface of the silicon-carbon negative electrode material, and the silicon nanowires are tightly stacked, and the graphite surface can no longer be seen.

[0131] Comparative Example 2

[0132] The difference between this comparative example and Example 1 is that the duration of molten salt electrolysis in S5 is 0.5 h.

[0133] Analysis showed that the SiO2 particles in the precursor were not deoxidized to form silicon, and silicon still existed in the form of oxide, and no silicon-carbon negative electrode material was generated.

[0134] Comparative Example 3

[0135] The difference between this comparative example and Example 1 is that the molten salt electrolysis time in S5 is 30 hours.

[0136] The nano-silicon content in the generated silicon-carbon negative electrode material is about 3wt%. Silicon nanowire clusters with a diameter of 150nm are generated on the graphite surface of the silicon-carbon negative electrode material. Compared with Example 1, this comparative example consumes 5 times the time to generate only silicon nanowires of the same size, and due to the longer time in the high temperature system, the silicon nanowires agglomerate, resulting in uneven distribution of silicon in the material.

[0137] Comparative Example 4

[0138] The difference between this comparative example and Example 1 is that the voltage applied to the molten salt electrochemical reaction in S5 is 0.5V.

[0139] Analysis showed that the SiO2 particles in the precursor were not deoxidized to form silicon, and silicon still existed in the form of oxide, and no silicon-carbon negative electrode material was generated.

[0140] Comparative Example 5

[0141] The difference between this comparative example and Example 1 is that the voltage applied during the molten salt electrochemical reaction is 5V.

[0142] The analysis showed that calcium impurities were introduced into the silicon-carbon negative electrode material. Due to the high voltage, the CaCl2 in the molten salt electrolyte decomposed to form metallic calcium, which reacted with the generated silicon to introduce calcium as an impurity.

[0143] Comparative Example 6

[0144] The difference between this comparative example and Example 1 is that the temperature of the molten electrolyte during the molten salt electrochemical reaction is 1200°C.

[0145] Analysis showed that the silicon nanowires on the graphite surface in the silicon-carbon negative electrode material were tightly aggregated, which was due to the uneven distribution of silicon caused by the excessively high molten salt temperature environment.

[0146] Comparative Example 7

[0147] The difference between this comparative example and Example 1 is that the carbon material is not subjected to acidification treatment.

[0148] The analysis shows that SiO2 is not deposited on the graphite surface in the precursor because the graphite surface without acid treatment does not contain active groups, and the SiO2 generated by hydrolysis cannot be deposited on its surface and exists in the solution in the form of particles. Therefore, the obtained precursor cannot be electrolyzed to generate silicon-carbon negative electrode materials.

[0149] Comparative Example 8

[0150] The difference between this comparative example and Example 1 is that the electrolyte is not pre-electrolyzed.

[0151] Analysis shows that the background current generated during the molten salt electro-deoxidation process is 1.5 times the background current during electrolysis after pre-electrolysis treatment. This is because the electrolyte that has not been pre-electrolysis treated contains impurities, which increases the background current while reducing the current efficiency.

[0152] Test example

[0153] The silicon-carbon negative electrode materials prepared in the above Examples 1 to 7 and Comparative Examples 1 to 8 were respectively assembled into CR2016 type button half-cells in the following manner. Subsequently, the assembled lithium-ion batteries were subjected to constant current charge and discharge capacity tests using a Blue Electric battery testing system CT2001A battery tester, with a current density of 100 mA / g and a voltage range of 0.005 V to 2 V.

[0154] The assembly method is as follows: the obtained silicon-carbon negative electrode material is mixed with conductive carbon black (Super P) and sodium carboxymethyl cellulose (CMC) in a mass ratio of 8:1:1, and then deionized water is added to make a slurry. The slurry is evenly coated on the copper foil by a coating machine, and then placed in an 80°C vacuum oven for drying for 12 hours and cut into discs with a diameter of 12 mm. In an argon glove box (H2O <0.1ppm, O2 <0.1ppm), a metal lithium sheet is used as a counter electrode and a reference electrode, the cut electrode sheet is used as a working electrode, a polypropylene microporous membrane celgard2400 is used as a diaphragm, and 1 mol / L LiPF6 solute is dissolved in an EC and DMC solvent containing 5wt% FEC (the volume ratio of EC and DMC is 1:1) as an electrolyte to assemble a CR2016 type button half-cell.

[0155] A. The results corresponding to Example 1 are as follows Figures 4 to 6 As shown. Figure 4 It can be seen that the first week charge capacity is 433.4mAh / g, the first week coulomb efficiency is 86.7%, and the capacity after 200 cycles is 424.3mAh / g, with a capacity retention rate of 98%. Figure 5 From the charge and discharge curve, it can be seen that after 100 cycles, the charging platform capacity is 354.5mAh / g, and the proportion of the total capacity is stable at about 82%. Figure 6From the rate performance, it can be seen that when the current density rises to 800mAh / g, the capacity retention rate is 27%. When the current density continues to increase, the sample capacity continues to decrease.

[0156] B. The cycle performance curve corresponding to Example 2 is as follows Figure 8 As shown in the figure, it can be seen that the charging capacity in the first week is 438.1 mAh / g, the coulomb efficiency in the first week is 86.14%, and the sample capacity after 100 cycles is 379.7 mAh / g, with a capacity retention rate of 86.7%.

[0157] C. The cycle performance curve corresponding to Example 3 is as follows Fig.11 As shown in the figure, it can be seen that the charging capacity in the first week is 714 mAh / g, the coulomb efficiency in the first week is 81.2%, and the sample capacity after 40 cycles is 359.7 mAh / g, with a capacity retention rate of 50.3%.

[0158] D. The first-week coulombic efficiency corresponding to Example 4 is 86.2%. After 50 cycles, the sample capacity is 348 mAh / g, and the capacity retention rate is 73.1%.

[0159] E. The first-week coulombic efficiency corresponding to Example 5 is 86.5%. After 40 cycles, the sample capacity is 430 mAh / g, and the capacity retention rate is 88.27%.

[0160] F. The first-week coulombic efficiency corresponding to Example 6 is 86%. After 40 cycles, the sample capacity is 425 mAh / g, and the capacity retention rate is 87%.

[0161] G. The first-week charge capacity of the sample corresponding to Example 7 is 319 mAh / g, the first-week coulombic efficiency is 86%, and the sample capacity after 50 cycles is 302 mAh / g, with a capacity retention rate of 94%. The silicon content in this sample is extremely low, so the capacity is lower than that of the sample with a high silicon content, but the capacity retention rate is relatively high.

[0162] H. The sample corresponding to comparative example 1 has a first-week charging capacity of 572.2 mAh / g, a first-week coulombic efficiency of 85.9%, and a sample capacity of 300.1 mAh / g after 50 cycles, with a capacity retention rate of 52.4%.

[0163] I. The sample corresponding to comparative example 3 has a first-week charging capacity of 400 mAh / g, a first-week coulombic efficiency of 85%, and a sample capacity of 326.2 mAh / g after 40 cycles, with a capacity retention rate of 81.5%.

[0164] J. The sample corresponding to comparative example 5 has a first-week charging capacity of 360.8 mAh / g and a first-week coulombic efficiency of 85.8%. After 30 cycles, the sample capacity is 352.2 mAh / g, and the capacity retention rate is 97%.

[0165] K. The sample corresponding to comparative example 6 has a first-week charging capacity of 397.8 mAh / g, a first-week coulombic efficiency of 86.2%, and a sample capacity of 269.7 mAh / g after 30 cycles, with a capacity retention rate of 68%.

[0166] L. The sample corresponding to comparative example 8 has a first-week charging capacity of 372.8 mAh / g, a first-week coulombic efficiency of 85.6%, and a sample capacity of 312.2 mAh / g after 30 cycles, with a capacity retention rate of 83.7%.

[0167] In summary, the solution provided by the present invention has at least the following advantages:

[0168] (1) In the preparation method of the silicon-carbon negative electrode material provided by the present invention, a silicon-carbon negative electrode material with controllable specific capacity and stable cycle performance can be obtained by controlling the silicon content in the precursor, thereby meeting the preparation requirements of lithium-ion batteries with different capacities.

[0169] (2) The present invention provides a one-step controllable method for preparing a silicon-carbon composite material, which simultaneously extracts and modifies silicon, has simple operation and a short cycle; and does not use metal catalysts, thereby avoiding product contamination.

[0170] (3) Compared with pure SiO2 as a precursor, the carbon material used in the present invention can greatly improve the conductivity of the precursor, accelerate the conduction of electrons between silicon oxide particles, and further accelerate the removal of oxygen ions, so that the silicon oxide in the precursor is fully deoxidized to generate silicon, thereby increasing the deoxidation rate.

[0171] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a carbon material and nano-silicon deposited on the surface of the carbon material; the content of the nano-silicon in the silicon-carbon negative electrode material is 1wt% to 10wt%, and the nano-silicon is prepared from nano-silicon oxide by a molten salt electrochemical method.

2. A method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The following steps are involved: A silicon oxide-carbon composite precursor is prepared into a cathode, and placed together with an anode in a molten electrolyte, and a voltage is applied to the cathode and the anode to obtain a silicon-carbon material with nano-silicon deposited on the cathode; Wherein, the silicon oxide-carbon composite precursor is a carbon material with nano silicon oxide deposited on the surface.

3. The preparation method according to claim 2, characterized in that: The preparation of the silicon oxide-carbon composite precursor comprises: mixing a silicon source and an acid-treated carbon material in an aqueous solvent to hydrolyze the silicon source to obtain a carbon material with nano silicon oxide deposited on the surface; Preferably, the silicon source includes at least one of the organosilicon compounds that can be hydrolyzed to form silicon oxide; Preferably, the mass ratio of the silicon source to the acid-treated carbon material is 0.001:1 to 0.95:1; Preferably, the volume ratio of the aqueous solvent to the silicon source is 200:1 to 5000:1; Preferably, the aqueous solvent comprises anhydrous ethanol and water in a volume ratio of 8:1 to 12:

1.

4. The preparation method according to claim 2, characterized in that: The preparation of the acid-treated carbon material comprises: acid-treating the carbon material with an acid, followed by drying; Preferably, the carbon material comprises at least one of graphite, carbon nanotubes and amorphous carbon; Preferably, the acid comprises at least one of concentrated nitric acid and concentrated sulfuric acid; Preferably, the temperature of the acidification treatment is 80°C to 120°C; Preferably, the acidification treatment is carried out under stirring conditions; more preferably, the stirring time is 20 h to 28 h.

5. The preparation method according to claim 2, characterized in that: The step of mixing the silicon source with the acid-treated carbon material in an aqueous solvent comprises: firstly ultrasonically mixing the acid-treated carbon material with the aqueous solvent to obtain a carbon dispersion; adjusting the hydroxide ion concentration of the carbon dispersion to 10 -1 mol / L~10 -3 mol / L; then adding the silicon source and stirring continuously, followed by solid-liquid separation and drying; Preferably, the hydroxide ion concentration of the carbon dispersion is adjusted by adding an alkaline solution to the carbon dispersion; Preferably, the alkaline solution comprises at least one of aqueous ammonia, sodium hydroxide and potassium hydroxide; Preferably, the stirring time is 20 h to 30 h.

6. The preparation method according to claim 2, characterized in that: The preparation of the silicon oxide-carbon composite precursor into a cathode comprises: fixing the silicon oxide-carbon composite precursor to a current collector; Preferably, the current collector is a metal conductor; Preferably, the metal conductor comprises at least one of stainless steel, low carbon steel, nickel, copper and molybdenum.

7. The preparation method according to claim 2, characterized in that: The anode is an inert electrode; Preferably, the anode comprises at least one of graphite, tin oxide and an inert alloy.

8. The preparation method according to claim 2, characterized in that: The electrolyte includes a monovalent or polyvalent mixed salt of a chloride salt or a fluoride salt; Preferably, the chloride salt comprises at least one of CaCl2, LiCl, NaCl and KCl; Preferably, the fluoride salt comprises at least one of CaF2, LiF, NaF and KF; Preferably, the electrolyte is first subjected to a pre-electrolysis treatment, and then the cathode and the anode are placed together in the electrolyte that has been subjected to the pre-electrolysis treatment and is in a molten state; Preferably, the voltage used for the pre-electrolysis treatment is 1V to 3V, and the time is 3h to 12h; Preferably, the temperature of the molten electrolyte is 400°C to 1000°C.

9. The preparation method according to claim 2, characterized in that: The applied voltage is higher than the precipitation voltage of silicon in silicon oxide and lower than the precipitation voltage of alkali metal in molten electrolyte; Preferably, the voltage is 1.5V to 3.5V; Preferably, the voltage is applied for a period of 1 hour to 24 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the silicon-carbon negative electrode material according to claim 1 or 2.

Citation Information

Cited By

  • Silicon-based negative electrode material, preparation method thereof and application of silicon-based negative electrode material in lithium ion battery

    CN121405095A

  • Method for preparing silicon-carbon negative electrode material through low-temperature molten salt electrolysis, silicon-carbon negative electrode and lithium ion battery

    CN122464425A